The Performance Evaluation of Natural Ventilation System at St John Mary Vianney Church as an Application of Health Ventilation - Maria Dita Indira Christabella Bija; Ary Deddy Putranto (Jurnal Mahasiswa Departemen Arsitektur, 2023)
A well performed natural ventilation in public buildings is crucial especially its contribution as health ventilation. Church of St. Yohanes Maria Vianney, used as the objectof this study holds a matter where the building has poor air circulation. The affecting factors are the ventilation’s orientation and ventilation’s ratio to building’s area and floor area. The analysis begins with 2 stages. First is to identify the shape, dimensions and placement of ventilations, then analyze the existing site subsequently make optimal design alternatives. Second, observations and inserts building section into the Energy 2D simulation to see the wind flow entering the building. Then, new design alternatives were put into the simulation to find out the kind of optimal ventilation for the best building's natural ventilation performance. The research results regarding air flow problems inside of the building still does not dilute and remove pollutants well. Therefore, in alternative design recommendations, ventilationsat the top of the building are added and change the permanent windows to pivoted windowsto increase the ratio of ventilations to the area of the facade to 50% and the ratio of ventilations to the area of the building to 19.3%, so that the distribution of fresh air throughout the building becomes optimal. Keywords: Natural Ventilation System, Air Flow, St. Yohanes Maria Vianney